2019
DOI: 10.1088/1755-1315/269/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Density of Clouded Leopard (Neofelis nebulosa) in Gunung Basor-Stong Utara Forest Reserve, Kelantan, Malaysia

Abstract: To date, much of the information on the clouded leopard study were more focus on Sunda clouded leopard. With the advance of technology, the use of camera trap had enhanced the opportunity for all researchers to study more deeply on species of interest in more intensely larger scale and cost benefit. This paper presents the density estimate of clouded leopard in Gunung Basor-Stong Utara Forest Complex (GB-SUFC). A total of 19 individuals of clouded leopard (14 males, 5 unknown) had been identified. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The closure test value from this study was similar to those found previously for clouded leopards and other carnivores (Karanth et al, 2006; Mondol et al, 2009; Singh & Macdonald, 2017). Our trapping period was shorter than most recent studies on clouded leopards (Mohamad et al, 2015; Singh & Macdonald, 2017; Ab Razak et al, 2019; Petersen et al, 2020), increasing the likelihood that the assumption of closure is valid. Our density estimate of 1.73 individuals per 100 km 2 is comparable to or lower than estimates from two sites in India (4.73/100 km 2 , Borah et al, 2014; 5.14/100 km 2 , Singh & Macdonald, 2017), one site each in Thailand (edge, 3.13/100 km 2 ; core, 5.06/100 km 2 ; Petersen et al, 2020), Malaysia (1.15/100 km 2 , Ab Razak et al, 2019) and Bhutan (0.40/100 km 2 , Penjor et al, 2018), two sites in Myanmar (0.60 and 3.05/100 km 2 , Naing et al, 2019) and two sites in Peninsular Malaysia (1.83 and 3.46/100 km 2 , Mohamad et al, 2015; Table 4, Supplementary Fig.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The closure test value from this study was similar to those found previously for clouded leopards and other carnivores (Karanth et al, 2006; Mondol et al, 2009; Singh & Macdonald, 2017). Our trapping period was shorter than most recent studies on clouded leopards (Mohamad et al, 2015; Singh & Macdonald, 2017; Ab Razak et al, 2019; Petersen et al, 2020), increasing the likelihood that the assumption of closure is valid. Our density estimate of 1.73 individuals per 100 km 2 is comparable to or lower than estimates from two sites in India (4.73/100 km 2 , Borah et al, 2014; 5.14/100 km 2 , Singh & Macdonald, 2017), one site each in Thailand (edge, 3.13/100 km 2 ; core, 5.06/100 km 2 ; Petersen et al, 2020), Malaysia (1.15/100 km 2 , Ab Razak et al, 2019) and Bhutan (0.40/100 km 2 , Penjor et al, 2018), two sites in Myanmar (0.60 and 3.05/100 km 2 , Naing et al, 2019) and two sites in Peninsular Malaysia (1.83 and 3.46/100 km 2 , Mohamad et al, 2015; Table 4, Supplementary Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Only a few ecological studies on the mainland clouded leopard have been published, primarily from radio-collared individuals in Thailand (Grassman et al, 2005; Austin et al, 2010) and Nepal (Dinerstein & Mehta, 1989), and more recently through camera trapping (India: Borah et al, 2014; Singh & Macdonald, 2017; Malaysia: Mohamad et al, 2015; Ab Razak et al, 2019; Bhutan: Penjor et al, 2018; Myanmar: Naing et al, 2019; Thailand: Petersen et al, 2020). Two of these seven camera-trapping studies used the Bayesian method to estimate density (Singh & Macdonald, 2017; Naing et al, 2019), four used the maximum likelihood approach (Borah et al, 2014; Mohamad et al, 2015, Ab Razak et al, 2019; Petersen et al, 2020) and one used both methods (Penjor et al, 2018). The estimated density ranged from 0.30 individuals (large areas of southern Bhutan; Penjor et al, 2018) to 5.14 individuals (Dampa Tiger Reserve, India; Singh & MacDonald, 2017) per 100 km 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Temporally, clouded leopards were active at night (nocturnal) (57%), and previous research showed similar results. Research in Malaysia (Rufino et al 2009) reported high activity of clouded leopards during the night (58%), while in Basor Mountain, Kelantan, nocturnal activity accounted for 73% (Hamirul et al 2019). In the concession area of Tigapuluh Hill, nocturnal activity accounted for 49% (Lestari 2018).…”
Section: Activity Patterns and Temporal Overlap Of Felidae-prey Inter...mentioning
confidence: 97%